Those who wish me dead - Koryta, Michael (Little, Brown, & Company, 2014)
"When 13-year-old Jace Wilson witnesses a brutal murder, he's plunged into a new life, issued a false identity and hidden in a wilderness skills program for troubled teens. The plan is to get Jace off the grid while police find the two killers. The result is the start of a nightmare. The killers, known as the Blackwell Brothers, are slaughtering anyone who gets in their way in a methodical quest to reach him. Now all that remains between them and the boy are Ethan and Allison Serbin, who run the wilderness survival program; Hannah Faber, who occupies a lonely fire lookout tower; and endless miles of desolate Montana mountains. The clock is ticking, the mountains are burning, and those who wish Jace Wilson dead are no longer far behind" --